Development of Mobile Learning (My Repro) Based on Contextual Teaching Learning to Improve Cognitive Understanding Senior High School Student - Saraswati, Shinta Almayra; Widiyaningrum, Priyantini; Indriyanti, Dyah Rini (Universitas Negeri Semarang)
During the current pandemic, the utilization of technology is needed in teaching and learning activities. It supports the emergence of Android-based learning innovations. Likewise, biology learning is accompanied by contextual learning related to everyday life. This study aimed to develop learning materials based on contextual teaching-learning and analyze the validity of learning media and cognitive understanding. This research used the 4-D model development method by Thiagarajan (Define, Design, Develop, Disseminate). The subjects were media experts and material experts, while the product's effectiveness was tested on 56 students of class XI MIPA at SMAN 1 Semaka. The results showed that the validation scores of material experts and media experts were 92.39% and 92.61%, respectively, with very valid criteria. Analysis of students' cognitive understanding showed high criteria with an average N-gain value of 0.70 (high criterion). Based on the research analysis results, it can be concluded that learning media mobile learning based on contextual teaching-learning have been valid and effectively used as a learning resource for high school students.